2012
DOI: 10.1007/s00374-012-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the soil microbiome to increase soil health and plant fertility

Abstract: A variety of soil factors are known to increase nutrient availability and plant productivity. The most influential might be the organisms comprising the soil microbial community of the rhizosphere, which is the soil surrounding the roots of plants where complex interactions occur between the roots, soil, and microorganisms. Root exudates act as substrates and signaling molecules for microbes creating a complex and interwoven relationship between plants and the microbiome. While individual microorganisms such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
480
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 914 publications
(500 citation statements)
references
References 127 publications
7
480
1
12
Order By: Relevance
“…Biotic constraints such as plant root exudates (14), plant immune signaling (15), and competition from native microorganisms (4) can play important roles in shaping soil microbiomes, but, in general, soil bacterial composition follows predictable patterns based on abiotic constraints, such as physicochemical soil parameters (16)(17)(18)(19). These constraints complicate soil microbiome manipulation and may restrict our ability to alter microbiome trajectories.…”
Section: Importancementioning
confidence: 99%
“…Biotic constraints such as plant root exudates (14), plant immune signaling (15), and competition from native microorganisms (4) can play important roles in shaping soil microbiomes, but, in general, soil bacterial composition follows predictable patterns based on abiotic constraints, such as physicochemical soil parameters (16)(17)(18)(19). These constraints complicate soil microbiome manipulation and may restrict our ability to alter microbiome trajectories.…”
Section: Importancementioning
confidence: 99%
“…Evidence demonstrating the close ties root exudates have on the microbial composition of the rhizosphere is mounting (Broeckling et al, 2008;Badri et al, , 2013aMicallef et al, 2009b;Chaparro et al, 2012Chaparro et al, , 2013, whereby many chemicals present in root exudates act as substrates, chemotactic or signaling molecules to orchestrate changes in microbial composition (Shaw, 1991;de Weert et al, 2002;Jain and Nainawatee, 2002;Horiuchi et al, 2005;Bais et al, 2006;Badri and Vivanco, 2009;Neal et al, 2012;Badri et al, 2013a). Recently, it was reported that the composition of Arabidopsis root exudates change following a plant developmental gradient (Chaparro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it was hypothesized that seedlings of roots release sugars as substrates for a wide diversity of microbes at early stages of development but as the plant ages it releases specific substrates and potentially antimicrobial compounds in an effort to select for particular microbial inhabitants of the rhizosphere (Badri et al, 2013a;Chaparro et al, 2013). This potential selection of microbes in the rhizosphere as the plant ages might be associated with the ability of beneficial microbes to suppress pathogenic ones (Mendes et al, 2011), trigger induced systemic tolerance to overcome abiotic stress (Selvakumar et al, 2012), increase the plant's innate immunity (Zamioudis and Pieterse, 2012), help in mineral nutrition (Bolan, 1991;van der Heijden et al, 2008) and in overall plant health (Berendsen et al, 2012;Chaparro et al, 2012). Here, we tested this hypothesis by analyzing the rhizosphere microbial composition of Arabidopsis by 454 pyrosequencing at four distinct physiological stages of development: seedling (four-five leaf stage), vegetative (rosette), bolting and flowering.…”
Section: Introductionmentioning
confidence: 99%
“…Breeding for plants that promote soil biology and chemistry, for example (McSwiney et al 2010), could become easier by applying genomic plant-breeding techniques alongside highthroughput microbiome sequencing (metagenomics) and noninvasive, below-ground plant analyses (Chaparro et al 2012). Breeding towards perennial lifestyle is another strategy for improving soil health, and is already showing great promise for improving soil health on farms (Glover et al 2010;Culman et al 2013).…”
Section: Ecosystem Servicesmentioning
confidence: 99%